Mobile device application for monitoring cyanobacteria harmful algal blooms using Sentinel-3 satellite Ocean and Land Colour Instruments. (November 2018) - Schaeffer, Blake A.; Bailey, Sean W.; Conmy, Robyn N.; Galvin, Michael; Ignatius, Amber R.; Johnston, John M.; Keith, Darryl J.; Lunetta, Ross S.; Parmar, Rajbir; Stumpf, Richard P.; Urquhart, Erin A.; Werdell, P. Jeremy; et al.
Abstract: Cyanobacterial harmful algal blooms (cyanoHAB) cause human and ecological health problems in lakes worldwide. The timely distribution of satellite-derived cyanoHAB data is necessary for adaptive water quality management and for targeted deployment of water quality monitoring resources. Software platforms that permit timely, useful, and cost-effective delivery of information from satellites are required to help managers respond to cyanoHABs. The Cyanobacteria Assessment Network (CyAN) mobile device application (app) uses data from the European Space Agency Copernicus Sentinel-3 satellite Ocean and Land Colour Instrument (OLCI) in near real-time to make initial water quality assessments and quickly alert managers to potential problems and emerging threats related to cyanobacteria. App functionality and satellite data were validated with 25 state health advisories issued in 2017. The CyAN app provides water quality managers with a user-friendly platform that reduces the complexities associated with accessing satellite data to allow fast, efficient, initial assessments across lakes. Highlights: Cyanobacterial blooms (CyanoHAB) are a human and ecological health concern. CyanoHABs are infrequently monitored to provide needed management information. The CyAN mobile app provides passive access to satellite data and basic analysis. Quantitative comparison against 2017 state advisories demonstrated app capability. CyAN app delivers spatial and temporal information on cyanobacteria concentration.